Hakikat Manusia Indonesia, Asumsi Kepribadian Konselor dan Konseli dalam Konseling Suryomentaraman - Tantri Safitri; Fatihatul Lutfiyah; Nurhayati Nurhayati; Fitriana Ningsih; Sova Abrori; Rusmiyati Rusmiyati (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to understand the essence of the Indonesian human and the personality assumptions of counselors and counselees in the Suryomentaraman counseling approach. This counseling emphasizes local wisdom and Indonesian spirituality rooted in true consciousness values. The research used a literature study method based on primary and secondary recent sources. The results show that the Suryomentaraman approach reconstructs the roles of counselor and counselee as conscious beings within the unity of life, rejecting Western binary dichotomies in counseling. This study’s implication enriches culturally-based counseling practices in Indonesia.